Formability and Damage in Electromagnetically Formed AA5754 and AA6111 - Golovashchenko, S.; Imbert, J. M.; Winkler, S. L.; Worswick, M. J. (Institut für Umformtechnik - Technische Universität Dortmund, 2004)
This paper presents the results of experiments carried out to determine the formability of AA5754 and AA6111 using electromagnetic forming (EMF), and the effect of the tool/sheet interaction on damage evolution and failure. The experiments consisted of forming 1mm sheets into conical dies of 40° and 45° side angle, using a spiral coil. The experiments showed that both alloys could successfully be formed into the 40?? die, with strains above the conventional forming limit diagram (FLD) of both alloys. Forming into the higher 45° cone resulted in failure for both materials. Metallographic analysis indicated that damage is suppressed during the forming process. Micrographs of the necked and fractured areas of the part show evidence that the materials do not fail in pure ductile fracture, but rather in what could be a combination of plastic collapse, ductile fracture and shear band fracture. The failure modes are different for each material; with the AA5754 parts failing by necking and fracture, with significant thinning at the fracture tip. The AA6111 exhibited a saw tooth pattern fractures, a crosshatch pattern of shear bands in the lower half of the part, and tears in the area close to the tip. Both areas showed evidence of shear fracture. This experimental study indicates that there is increased formability for AA5754 and AA6111 when these alloys are formed using EMF. A major factor in this increase in formability is the reduction in damage caused by the tool/sheet interaction.
Keywords: damage; electromagnetic sheet metal forming; formability; 620; 670